Kontribusi Kepemimpinan, Lingkungan Kerja, Disiplin Kerja, dan Etos Kerja terhadap Kinerja Pegawai di Lingkungan Fakultas Teknik dan Kejuruan Universitas Pendidikan Ganesha. Tesis, Administrasi Pendidikan, Program Pascasarjana, Universitas Pendidikan Gane - Trisnayanti, K. Ary; Purnamawati, I Gusti Ayu; Sunu, I Gusti Ketut Arya (Jurnal Administrasi Pendidikan Indonesia, 2023)
This study aims to 1) analyze how much leadership contributes to employee performance in the Undiksha Faculty of Engineering and Vocational environment, 2) analyze how much the work environment contributes to employee performance in the Undiksha Faculty of Engineering and Vocational environment, 3) analyze how much work discipline contributes to employee performance in the Undiksha Faculty of Engineering and Vocational environment, 4) analyze how much the work ethic contributes to employee performance in the Undiksha Faculty of Engineering and Vocational environment, 5) analyze how much the contribution of leadership, work environment, work discipline, and work ethic to employee performance in Undiksha Faculty of Engineering and Vocational. This research is a non-treatment or ex-post facto research because it does not treat the variables and only takes data directly. The population in this study were all employees in the Faculty of Engineering and Vocational Education at the Ganesha University of Education, consisting of 33 people. This study used the sampling method of saturated sampling so that the sample in this study was 33 people. data collection used is a questionnaire method. The data obtained were analyzed using multiple regression analysis techniques and then continued with the determinant test. The results of the study show that 1) There is a significant contribution of leadership to employee performance in the Undiksha Faculty of Engineering and Vocational environment, 2) There is a significant contribution of the work environment to employee performance in the Undiksha Faculty of Engineering and Vocational environment, 3) There is a significant contribution of work discipline on employee performance in the Undiksha Faculty of Engineering and Vocational environment, 4) There is a significant contribution of work ethic to employee performance in the Undiksha Faculty of Engineering and Vocational environment, 5) There is a significant contribution of leadership, work environment, work discipline, and work ethic to employee performance in the Faculty of Engineering and Vocational Undiksha.